Peran High Performance Work System Terhadap Employee Engagement dan Employee Resilience: Studi Literatur - Ine Suwartining Wulandari; Agus Frianto (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine the role of high-performance work systems on employee engagement and employee resilience and also the effect of employee engagement on employee resilience. Literature studies are based on 23 international journals and data are collected using search engine methods. The results showed that high-performance work systems have a positive effect on employee engagement and employee resilience and employee resilience plays an important role in supporting this influence. If high performance work systems (HPWS) is implemented properly, the factors that influence it are considered, and there is a balance between the goals of the employee and the organization, then employee participation is in line with the company’s goals in building a superior company.